Knowledge Of Families Toward Type 1 Diabetes Among Children In AL-Diwaniyah City, Iraq: Cross-Sectional Study –College of Medicine/ University Of AL-Qadisiyah - Obayes, Hawraa Qasim; Al-khalidi, Fatima (International Journal of Membrane Science and Technology, 2023)
Background: Type 1 diabetes is one of the most common chronic diseases in childhood, that is considered a challenge for parents especially when the child is not developmentally able to manage the disease independently. Since optimal glycemic control is required to prevent acute and long-term diabetes-related complications and enhance school performance, the importance of involving adults in the child diabetes management is essential. Aim of the study: The current study aimed to evaluate the knowledge, regarding children with T1DM among families living in Diwaniyah city. Subjects and Method: A cross sectional study conducted in Al Diwaniyah governate, Iraq on a sample of 400 caregivers of type 1 diabetes mellitus diagnosed children for a period of three months. Structured questionnaires were used for Knowledge. Chi -square test was applied to find the significant association between qualitative variables. Independent t test and one way ANOVA were applied to illustrate a significant difference between quantitative variable. In all Statistical analyses, a p value equal or below 5% was considered significant. Results: Majority of caregivers; 192 (48%), were in their forties and married. Mothers 239 (59.8%) were the main caregivers, more than half of the studied sample 237(59.3%) had university or institute educational attainment. The average score for knowledge was 9.39±2.9 scores ranging from 0-12 score. Poor knowledge was found among 64 (16%) of caregivers, while 42(10.5%) and 294(73.5%) scored moderate and good knowledge respectively. Education and urban residency were significantly associated with good knowledge. Lower HbA1C level was seen associated with good diabetes knowledge. Conclusion: Although good knowledge were reported. Such discrepancy requires an increase in public awareness about the T1DM. Using modern technology to disseminate the correct information to caregivers.